Model Pengembangan Kultur Kewirausahaan di Sekolah Menengah Kejuruan - Nuryadin Eko Raharjo; V. Lilik Hariyanto; Amat Jaedun (Faculty of Engineering, Universitas Negeri Yogyakarta, 2014)
The objectives of this study were to develop entrepreneurial culture and to acquire the entrepreneurial culture development model in Vocational High Schools. The first stage is prototype development consisting of: (1) literature review (2) prototype development (3) prototype revision using Focussed Group Discussion (FGD), (4) manual and mapping instruments development (5) validation and verification through FGD, (6) self-evaluation and planning (7) experiment. Meanwhile, the second stage was the final to examine the effectiveness of the model consisting of: (1) model socialization (2) manual and instrument models validation through FGD, (3) self-evaluation and entrepreneurial culture development planning,(4) experiment, (5) revision and the manual for implementation, (6) model dissemination. The results of this study were (1) the entrepreneurial culture could be developed through internalization of entrepreneurship values into school culture, (2) the internalization of entrepreneurial characters includes: (a) mind-set (b) heart-set (c) action-set, (3) the approaches used in the internalization were figures, culture, and structures approaches, (4) the school culture as the target of the internalization consists of three layers, namely: (a) artifacts layer (b) the values and beliefs layers, (c) the assumption layer.